Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films